(Gd, Lu)AlO3:Dy3+ and (Gd, Lu)3Al5O12:Dy3+ as high-temperature thermographic phosphors. (7th February 2019) - Hertle, Ellen; Chepyga, Liudmyla; Osvet, Andres; Brabec, Christoph J; Batentschuk, Miroslaw; Will, Stefan; Zigan, Lars
Abstract: A comparative investigation of the thermographic properties of Dy 3+ -doped gadolinium aluminum perovskite GdAlO3 (GAP) and gadolinium aluminum garnet Gd3 Al5 O12 (GAG) was performed with special regard to the suitability of these materials for surface thermometry in harsh measurement environments. The phosphors were synthesized by conventional high-temperature solid-state method using lithium fluoride (LiF) as a flux. The effects of substituting Gd 3+ by Lu 3+ ions on the stability of the garnet structure and the luminescence properties of the phosphors were investigated. An efficient energy transfer from Gd 3+ to Dy 3+ resulted in significantly stronger Dy 3+ emission obtained through Gd 3+ excitation at 275 nm compared to direct excitation of Dy 3+ at 352 nm. The luminescence intensity of GAP:Dy 3+ with Lu 3+ substitution was three times higher at room temperature compared to GAP:Dy 3+ . Due to this intensity enhancement, the range of temperature measurements by the intensity ratio and decay time methods was extended from 900 K to 1100 K. The luminescence intensity of (Gd, Lu)AG:Dy 3+ was doubled at room temperature compared to (Gd, Lu)AP:Dy 3+ and the limit for reliable temperature measurements by the above mentioned methods was increased up to 1600 K.